Methodological guidelines to explore altered states of consciousness and anomalous experiences (Archives of Clinical Psychiatry, 2003)
Anomalous experiences (AE) (uncommon experiences or one that is believed to deviate from the usually accepted explanations of reality: hallucinations, synesthesia, experiences interpreted as telepathic...) and altered states of consciousness (ASC) are described in all societies of all ages. Even so, the scientists have long neglected the studies on this theme. To study AE and ASC is not necessary to share the believes we discuss, they can be investigated as subjective experiences and correlated like any other set of data. This article presents some methodological guidelines to explore these experiences, among them: to avoid prejudice approaches and to "pathologize" the unusual, the value of a theory and a comprehensive review of literature, using various concepts of pathology and normality, the investigation of clinical and non-clinical populations, development of new search instruments, to be careful to choose terms and to decide causal nexus, to distinguish experiences and interpretations, to take into account the role of culture, to evaluate the validity and reliability of reports, and the last, but not least, creativity and diversity in choosing methods.